The seasonal variation of interest rates - Diller, Stanley (New York : National Bureau of Economic Research; distributed by Columbia University Press, 1969)
A study of seasonal variation of interest rates. It contributes to understanding of the money market and the behavior of interest rates.
obn 24/01/2019
Loans
Keywords: Interest rates